Critical Thinking and Student Well-Being: An Approach in University Students - José Carlos Vázquez-Parra; Paloma Suárez-Brito; Patricia Esther Alonso-Galicia; Arantza Echaniz-Barrondo (Societies, 2023)
Human well-being is a dynamic and changing concept as it depends on personal, social, cultural, and political factors and varies over time according to individual circumstances. Therefore, it is essential to address this issue from a comprehensive and multidisciplinary approach, seeking that individuals, from an early age, manage to develop skills and attitudes that allow them to achieve a balance in their lives. This article presents the results of the measurement of students’ perceived achievement of the competence of complex thinking in a subject focused on human development. Specifically, the research sought to identify whether there is a relationship between the level of critical thinking and the acquisition of skills associated with human well-being. The selection of critical thinking is based on the fact that this cognitive ability is one of the subcompetencies included in complex thinking. The sample was a group of university students from different disciplines and educational levels. Methodologically, descriptive analyses were made on the means of students’ responses to a validated instrument measuring the perceived achievement of complex thinking competency and its subcompetencies and the final evaluations of the students’ course. In conclusion, an improvement in the perception of achievement of complex thinking competency and its subcompetencies is demonstrated in the students, with critical thinking that achieved the best means, its increase being significant for the whole group and for women but not for men. In this sense, although it was not possible to demonstrate a statistically significant relationship between the development of this subcompetency and the acquisition of tools associated with well-being, data showing a possible association between these elements were obtained.